Workplace Violence and its Associated Factors among Nurses - Pandey, Manisha; Bhandari, Tulsi Ram; Dangal, Ganesh (Journal of Nepal Health Research Council, 2018)
Background: Workplace violence among nurses is prevalent worldwide. If nurses become aware of the workplace violence and its risk factors then only they can protect themselves. This study assessed the prevalence of workplace violence and its associated factors among nurses in Pokhara, Nepal. Methods: A hospital-based descriptive cross-sectional study was conducted in Pokhara. The required sample size of the study was 200 nurses. We adopted self-administered questionnaire developed by International Labor Office, International Council of Nurses, World Health Organization (WHO), and Public Services International. Out of 21 hospitals of Pokhara, we selected five hospitals using simple random sampling method. The number of nurses in each hospital was fixed proportionately considering the total number of employed nurses. Individual nurses were selected on the first meet first basis to gain the required number. Results: Two-thirds (64.5%) nurses experienced some type of violence in the last six months at their workplace. The proportion of verbal violence was higher (61.5%) compared to the physical (15.5%) and sexual violence (9%). Most perpetrators of the violence were the relatives of patients and hospital employees. Age of nurses and working stations had statistically significant association with workplace violence (p-value < 0.05). Conclusions: Workplace violence among nurses is a noteworthy problem in Pokhara whereas nearly two-thirds of nurses faced some type of violence in last six months. It is an urge to widen awareness level of nurses on the violence thus, they can take precaution themselves and ask hospital administration and other stakeholders to address the workplace violence.